2019
DOI: 10.2147/ott.s198945
|View full text |Cite
|
Sign up to set email alerts
|

<p>Second-generation EGFR and ErbB tyrosine kinase inhibitors as first-line treatments for non-small cell lung cancer</p>

Abstract: The discovery that mutations in the EGFR gene are present in up to 50% of patients with lung adenocarcinoma, and the development of highly efficacious EGFR tyrosine kinase inhibitors (TKIs), has revolutionized the way this common malignancy is treated. Three generations of EGFR TKIs are now approved for use in EGFR mutation-positive non-small cell lung cancer (NSCLC); the first-generation agents erlotinib, gefitinib, and icotinib; the second-generation ErbB family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 97 publications
1
29
0
Order By: Relevance
“…Although gefitinib showed the most obvious inhibitory effect on the phosphorylation of EGFR and ERK of these EGFR‐TKIs, especially in HMVECs, erlotinib was selected for further experiments. This is because erlotinib is a more widely used first‐generation EGFR‐TKI in clinical conditions than gefitinib .…”
Section: Resultsmentioning
confidence: 99%
“…Although gefitinib showed the most obvious inhibitory effect on the phosphorylation of EGFR and ERK of these EGFR‐TKIs, especially in HMVECs, erlotinib was selected for further experiments. This is because erlotinib is a more widely used first‐generation EGFR‐TKI in clinical conditions than gefitinib .…”
Section: Resultsmentioning
confidence: 99%
“…Several oncogenic drivers have been identified in lung adenocarcinoma, including mutations in the epidermal growth factor receptor (EGFR) [ 8 ], fusions of anaplastic lymphoma kinase (ALK) [ 9 ], and rearrangements of ROS proto-oncogene 1 receptor tyrosine kinase (ROS1) [ 10 ]. Accumulating evidence demonstrated that mutations of EGFR were identified in 15–30% of lung adenocarcinomas in Caucasians [ 11 ] and 40–60% in East Asians [ 12 14 ], indicating that the frequency of activated mutations of EGFR depends on ethnicity.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to this finding, the MTB, based on scarce literature data and taking into account the lack of other validated efficient drugs in a fifth-line setting for NSCLC, suggested to offer the patient Afatinib treatment, a second generation pan-ErbB tyrosine kinase inhibitor, at 40mg/day, as already described in NSCLC with EGFR mutation 7 . This treatment had actually been reported to display some efficacy in a lung squamous cell carcinoma patient with a tumor missense mutation in the ERBB4 gene (p.Arg847His) 8 , and in an urothelial carcinoma patient with ERBB3 missense mutations 9 .…”
Section: Research Lettermentioning
confidence: 99%